Pleiotypic Control by Cyclic AMP: Interaction with Cyclic GMP and Possible Role of Microtubules - Kram, Raphael (1973)
Previous studies have shown that exogenous dibutyryl cyclic AMP inhibits the uptake of uridine, leucine, and 2-deoxyglucose by cultured mouse fibroblasts. 3′:5′-cyclic GMP is shown here to counteract these inhibitory effects as well as the inhibition of precursor transport and leucine incorporation into proteins produced by prostaglandin E(1). We conclude, therefore, that cyclic GMP antagonizes the “pleiotypic” effects of cyclic AMP in these cells. Colcemid and vinblastine, but not cytochalasin B, reverse the transport inhibition caused by cyclic AMP without affecting the intracellular concentrations of cyclic AMP. These results suggest the possibility that cyclic AMP regulates the membrane transport of certain substrates by influencing the organization of microtubules.